Pengaruh Sharia Compliance Terhadap Kinerja Perbankan Syariah - Dita Fitri Nurjannah; Sigid Eko Pramono; Mahbubi Ali (Akuntabilitas, 2020)
This study aims to determine the effect of Sharia Compliance (SC) on the performance of Islamic banking in Indonesia. This type of research is a descriptive verification study, with the method of collecting secondary data obtained from annual reports or annual reports published by Islamic Commercial Banks (BUS) for the 2014-2018 period. Sampling was using by purposive sampling. The number of samples used was 11 BUS in Indonesia with five study periods, so that 55 observant data were obtained. The statistical analysis used is descriptive analysis and simple linear regression analysis, preceded by a normality test and a linearity test, then a regression test using the F test and t test with a significance level of 5%. The results of the study using simple linear regression showed that SC has a positive effect on Sharia banking performance in Indonesia. This means that the higher the SC level, the BUS performance level will also increase.